The world is flat : a brief history of the twenty-first century - Friedman, Thomas L.; Wyman, Oliver (New York : Audio Renaissance, 2005)
Translating complex foreign policy and economic issues, Friedman demystifies the new "flat" world for listeners, making sense of the advances in technology and communications, and showing how governments and societies can, and must, adapt.
Subtitle from container.
Unabridged.
In container (16 cm.).
Read by Oliver Wyman.
Keywords: Diffusion of innovations; Globalization -- Economic aspects; Globalization -- Social aspects; Information society; Audiobooks